2020
DOI: 10.1101/2020.06.02.130856
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into the structure and role of seed-borne bacteriome during maize germination

Abstract: Seed germination events modulate microbial community composition, which ultimately influences seed to seedling growth performance. Here we assess the seed-borne bacteria community in disinfected and non-disinfected maize seeds and seedlings. Using a gnotobiotic system, sodium hypochlorite (1.25%, 30 min) treated-seeds showed a reduction of bacteria population size and an increase of bacteria community diversity associated with selective suppression of Burkholderia related taxon. The shift in the bacteria commu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The dynamics of the seed microbiome during maturation, transferred to the next generation, and their influence on the seedlings have been the subject of many studies (Shade et al, 2017;Dos Santos et al, 2021;Kim and Lee, 2021;Bintarti et al, 2022). Endophytes of rice plants and seeds have also garnered recent attention.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of the seed microbiome during maturation, transferred to the next generation, and their influence on the seedlings have been the subject of many studies (Shade et al, 2017;Dos Santos et al, 2021;Kim and Lee, 2021;Bintarti et al, 2022). Endophytes of rice plants and seeds have also garnered recent attention.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Heijo et al (2021) added to the understanding of plant-endophyte interactions in agroecosystems by investigating the effect of diazotrophic bacterial endophyte inoculation on sweet sorghum performance depending on nitrogen fertilization doses and the sorghum cultivar. Figueiredo dos Santos et al (2021) showed that maize seedborne bacteria are crucial for germination and development of maize seedlings. Combining in vitro functional screening for plant growth promotion with whole genome sequencing provided new insights into the mechanisms of two tropical Bacillus inoculant strains on different maize genotypes (Vieira Velloso et al 2020).…”
mentioning
confidence: 99%